1992
DOI: 10.1073/pnas.89.3.1109
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of brain glucose concentrations in humans by 13C NMR spectroscopy.

Abstract: Glucose is the main fuel for energy metabolism in the normal human brain. It is generally a ed that glucose transport into the brain is not rate-limiting for metabolism. Since brain glucose concentrations cannot be determined directly by radiotracer techniques, we used 13C NMR spectroscopy after infusing enriched D-[1-_3C]glucose to measure brain glucose concentrations at euglycemia and at hyperglycemia (range, 4.5-12.1 mM) in six healthy children (13-16 years old). Brain glucose concentrations averaged 1.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
196
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(206 citation statements)
references
References 34 publications
8
196
1
1
Order By: Relevance
“…The brain glucose concentration and transport constants are consistent with transport not being rate-limiting for resting brain metabolism at plasma levels >3 mM. 17,49 …”
Section: Steady-state Measurements Of Glucose Transport Kineticssupporting
confidence: 53%
See 2 more Smart Citations
“…The brain glucose concentration and transport constants are consistent with transport not being rate-limiting for resting brain metabolism at plasma levels >3 mM. 17,49 …”
Section: Steady-state Measurements Of Glucose Transport Kineticssupporting
confidence: 53%
“…[17][18][19]28,33 In 1994 it was first demonstrated that in vivo 13 C NMR may be used to measure the rate of glutamine labeling from 1-13 C glucose in human occipital/parietal cortex. 18,27 However the rate of the glutamate/glutamine cycle was not uniquely determined from these first experiments due to the inability to distinguish the glutamate/glutamine cycle from other sources of glutamine labeling in the glia.…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, a 'normal' physiological plasma glucose concentration (5-7 mM) correlates with a brain extracellular glucose concentration of approximately 2 mM, by invasive microdialysis studies [1,17,27], resulting in a linear 3:1 ratio between plasma and tissue glucose concentrations [27]. Plasma glucose concentrations of <3 mM lead to impaired cognitive function [3,4], and limitations of glycolysis [17,18].…”
Section: Comparison Of In Vitro Glucose Ambient Levels and In Vivo CLmentioning
confidence: 99%
“…Plasma glucose concentrations of <3 mM lead to impaired cognitive function [3,4], and limitations of glycolysis [17,18].…”
Section: Comparison Of In Vitro Glucose Ambient Levels and In Vivo CLmentioning
confidence: 99%